Effect of slope and footwear on running economy and kinematics - Lussiana, T.; Fabre, N.; Hébert-Losier, K.; Mourot, L. (Applied physiology, nutrition, and metabolism, 2013)
Lower energy cost of running (Cr) has been reported when wearing minimal (MS) vs traditional shoes (TS) on level terrain, but the effect of slope on this difference is unknown. The aim of this study was to compare Cr, physiological, and kinematic variables from running in MS and TS on different slope conditions. Fourteen men (23.4 ± 4.4 years; 177.5 ± 5.2 cm; 69.5 ± 5.3 kg) ran 14 5‐min trials in a randomized sequence at 10 km/h on a treadmill. Subjects ran once wearing MS and once wearing TS on seven slopes, from −8% to +8%. We found that Cr increased with slope gradient (P < 0.01) and was on average 1.3% lower in MS than TS (P < 0.01). However, slope did not influence the Cr difference between MS and TS. In MS, contact times were lower (P < 0.01), flight times (P = 0.01) and step frequencies (P = 0.02) were greater at most slope gradients, and plantar‐foot angles – and often ankle plantar‐flexion (P = 0.01) – were greater (P < 0.01). The 1.3% difference between footwear identified here most likely stemmed from the difference in shoe mass considering that the Cr difference was independent of slope gradient and that the between‐footwear kinematic alterations with slope provided limited explanations.